Drought management plans in the Spanish river basins - Estrela T.; Vargas E. (Drought management: scientific and technological innovations, 2008)
During the past recent years, Spain has suffered a significant dry season, which still persists nowadays. Drought events occur frequently, seriously impacting the environment and water availability, causing important socio-economic impacts. These situations highlight the need of a planned and integrated management of water resources, in order to prevent and mitigate the drought linked negative effects. In order to minimise the negative environmental, economic and social impacts caused by drought, the Spanish water policy framework introduces the development of a hydrological indicator national system, which acts as a reference for River Basin Authorities to establish Drought Management Plans (DMP). Following an important launching period in 2006, the Plans were approved through Ministerial Order in March 2007. The DMPs include mitigation measures to be applied in the different water resources management systems, which represent water planning units within river basins. Prior to their approval, the Plans were submitted through a Strategic Environmental Assessment (SEA) and the consequent public participation and dissemination process. Since their implementation, the DMPs have provided the bases for a planned drought management, establishing drought phases and describing the measures that should be progressively applied and the needed monitoring and follow-up processes. Furthermore, the Plans include methods and measures previously agreed by all participating stakeholders: civil society, public administration and scientific community. The main results include a more control and planned management of droughts that has allowed prioritising uses, ensuring public urban supply and minimising environmental degradation. Therefore, the DMPs represent important reference documents that can help in reducing drought impacts, through a planned and participative approach. This article describes the DMPs development process, their contents and the results obtained since their implementation.
1. International Conference Drought Management: Scientific and Technological Innovations, 2008/06/12-14, Zaragoza (Spain)